2004
DOI: 10.1103/physrevb.70.224403
|View full text |Cite
|
Sign up to set email alerts
|

Colossal electroresistance of aPr0.7Ca0.3MnO3thin film at room temperature

Abstract: The electronic conduction through a Pr 0.7 Ca 0.3 MnO 3 thin film is investigated by measurements using dc and pulsed biases. Semiconducting Pr 0.7 Ca 0.3 MnO 3 films sandwiched by electrodes show both hysteretic and asymmetric behaviors in current-voltage characteristics. The observed conduction characteristics exhibit the spacecharge-limited-current effect, and the hysteretic behavior can be ascribed to a carrier trapping and detrapping of the trap sites in the manganite. The hysteresis induces a colossal el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
158
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(165 citation statements)
references
References 15 publications
5
158
2
Order By: Relevance
“…T he past decades have witnessed dramatic discoveries in carrier-doped, strongly correlated complex oxides, typified by the emergence of high-temperature superconductivity in doped antiferromagnetic (AFM) cuprates and colossal magnetoresistance (CMR) in doped manganites 1,2 ; interestingly, reversible resistance switching induced by external electric fields on various manganites shows large electroresistance (ER) response and provides a great potential as an emerging nonvolatile memory technology [3][4][5][6] . Although the detailed mechanism of high-temperature superconductivity remains to be understood, CMR effect in the manganites is known to result from coexisting and competing ferromagnetic (FM) metallic and AFM-insulating phases in the CMR regime 7,8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T he past decades have witnessed dramatic discoveries in carrier-doped, strongly correlated complex oxides, typified by the emergence of high-temperature superconductivity in doped antiferromagnetic (AFM) cuprates and colossal magnetoresistance (CMR) in doped manganites 1,2 ; interestingly, reversible resistance switching induced by external electric fields on various manganites shows large electroresistance (ER) response and provides a great potential as an emerging nonvolatile memory technology [3][4][5][6] . Although the detailed mechanism of high-temperature superconductivity remains to be understood, CMR effect in the manganites is known to result from coexisting and competing ferromagnetic (FM) metallic and AFM-insulating phases in the CMR regime 7,8 .…”
mentioning
confidence: 99%
“…An analogous response caused by mixed-phase coexistence in non-magnetic, uncorrelated oxides is found in the relaxor family of ferroelectrics, in which large dielectric and piezoelectric responses are observed near morphotropic phase boundaries 9,10 . In thin-film BiFeO 3 , epitaxial strain leads to the formation of a nanoscale, mixedphase ensemble of two crystal structures that can be reversibly transformed between each other with electric fields, leading to large piezoelectric responses 11,12 . Although these examples (as a direct consequence of mixed-phase coexistence) all occur in systems that are insulating (at least until chemically doped), we extend the same concept to metallic systems of FeRh in this report.…”
mentioning
confidence: 99%
“…This is especially true for the switching across metal-Pr 0.7 Ca 0.3 MnO 3 (PCMO) interfaces. 3,4,5,6 Several models, i.e. bulk phase-separation, 3 carrier-trapping in pre-existing metallic domains, 7,8 and field-induced lattice defects, 4 have been proposed.…”
mentioning
confidence: 99%
“…This change in electrical resistance induced by electric current/electric field is known as electroresistance (ER). In most of the previous work ER was observed in thin films and single crystal manganites with a charge ordered insulating (COl) state [6][7][8][9][10][11]. Only a few studies were reported on the electroresistance in polycrystalline manganites [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%